The Role of Parental Involvement in Academic Achievement - Thomas, Jesse (My University, 2010)
Improving the academic achievement of students is a constant goal of America’s school system. Over the course of American history, many studies have been conducted to determine influences that can be manipulated to trigger a positive effect on learning. Some studies concluded that parental involvement in children’s education helps academic achievement. This research was meant to determine the relationship between parental involvement and academic achievement and how parents can be best utilized in their child’s education. Previous studies performed insist parental involvement plays a positive role in academic achievement. Careful scrutinizing of such research shows parental involvement does play a role in academic achievement, but it may not be in the manner most educators expect. The research attempted to show how parents can be involved, how much they should be involved, and the impact of parental involvement in academic achievement of their children. This study looked at three categories: volunteering, supervision and expectations to determine the impact each have on the academic achievement of the students.
To see paper in its entirety contact archives@goucher.edu or call (410)337-6075.
Keywords: Education -- Research papers (Graduate); Education -- Parent participation -- Research; Academic achievement -- Research